Pengaruh Penempatan Aparatur Sipil Negara terhadap Kinerja Aparatur Pelayanan Publik di Kecamatan Singkil Kota Manado - Maliki, Tiara Murtifa; Ogotan, Martha; Laloma, Alden (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract : This study aims to determine the influence of job placement on the performance of civil state apparatus in the sub-district of Singkil, city of Manado. This research uses quantitative method. Respondents in this study numbered 56 civil state apparatus in sub-district of Singkil, city of Manado. Instrument and data collection techniques used are questionnaires and assisted by interviews and observation. Analytical techniques used for testing the hypothesis is the analysis of correlation coefficient and simple linear regression analysis with the help of SPSS 21.0 data processing program. Based on the results of this study work placements have a significant effect on the performance of ASN in the sub-district of Singkil, city of Manado. This can be seen from the t-test results In Table Table Coefficients a job placement value of 0.00 <0,05 so H0 is rejected, which means work placement partially significant effect on ASN performance variable In the sub-district office of Singkil, city of Manado. If incorporated into a simple regression equation then the value is Y = 15.845 + 0.562 X + e, with the value of the correlation coefficient (R) of 0,554. This number indicates that the relationship between the independent variable (X) and the dependent variable (Y) in the "moderate" category of employee placement on ASN performance as suggested by Sugiyono is at intervals (0.00 to 0.199), and the correlation coefficient of determination (R2 ) Obtained is 0.307 which shows that the effect of work placement on ASN performance is 30.7%Keywords: Job placement, ASN performance, sub-district of Singkil, city of Manado